Clinical practice guidelines for the prevention and management of frailty: A systematic review. (7th October 2021) - Zheng, Lufang; Li, Guichen; Qiu, Yiming; Wang, Cong; Wang, Chunyan; Chen, Li
Abstract: Aims: To systematically search for clinical practice guidelines focusing on the prevention and management of frailty, to evaluate their methodological quality and to synthesize the consensus recommendations. Design: A systematic review. Data Sources: Guideline websites, related professional association websites and electronic databases were systematically searched through 4 November 2020. Review Methods: We evaluated the methodological quality of the eligible guidelines using the Appraisal of Guidelines Research and Evaluation II (AGREE II). Two reviewers synthesized the consensus recommendations proposed by at least two guidelines. Results: Eight guidelines met the eligibility criteria and were included in the review. The mean scores of the six domains were as follows: the 'scope and purpose' domain scored 88.0%, the 'clarity of presentation' domain scored 81.9%, the 'stakeholder involvement' domain scored 63.4%, the 'editorial independence' domain scored 62.2%, the 'rigour of development' domain scored 61.1% and the 'applicability' domain scored 57.8%. In total, we synthesized 23 recommendations for the prevention and management of frailty that are consistent among the included guidelines. Conclusions: The number of clinical practice guidelines for the prevention and management of frailty is limited. The methodological quality of existing guidelines needs to be improved. Our synthesized findings provide an intuitive, convenient and summative reference resource for frailty prevention and management. It' is worth noting that recommendations described in the included guidelines require additional detail. Impact: Although the prevention and management of frailty is urgent, there is currently a lack of evidences guiding these processes, especially in the prevention. The methodological quality of existing guidelines is insufficient, and the recommendations described in the guidelines require additional detail. Therefore, users of these guidelines, especially nurses, should make a careful decision according to the specific situation when using. Nurses also have a key role in providing more clinical evidences for the improvement of the quality of the guidelines.